Star-shaped sucrose-capped CaO nanoparticles from Azadirachta indica: A novel green synthesis. Issue 5 (4th May 2017) - Jagadeesh, Dani; Prashantha, Kalappa; Shabadi, Rajashekhara
ABSTRACT: Calcium oxide (CaO) is an essential compound because of its application as catalyst and as effective chemisorbent for toxic gases. In this research, sucrose-capped CaO nanoparticles (S-CaO NPs) were prepared via simple eco-friendly green synthesis method at room temperature. Samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). SEM images showed that calcium oxide nanoparticles (CaO NPs) were nanoscale in morphology. TEM images illustrated that produced CaO nanoparticle are semicylindrical star-shaped particles that had a mean particle diameter of about 100 nm with a length of 500 nm. Further, the prepared CaO NPs were tested for their antimicrobial activity. Overall studies indicated that this method could be used for the production of CaO NPs on large scale as a cheap and convenient way, without using any surfactant, organic medium, or complicated instrumental procedure. These bioactive nanoparticles also inhibit the biofilm formation and may have future applications as a cheap and non-toxic antimicrobial drug for skin care products and biomedical applications.